Predictive tools and strategies for establishing risk-based Microbiological Criteria in Foods - Valero A. (Food safety challenges for mediterranean products, 2015)
One of the fundamental objectives of food legislation is the assurance of an appropriate level of health protection, as already stated in the EC Regulation No. 178/2002 concerning the food safety and hazard analysis policies. However, the increasing food exports between countries to a large number of consumers give rise to the need of a further harmonization of the control procedures leading to increase food safety. To date, due to the lack of homogeneity in the development of scientific risk assessments for different pathogens in foods, a sufficiently cohesive and integrated food safety policy has not been yet developed. To make feasible the implementation of food safety management schemes, the routine and successful use of software applications by the food industry, governments or educational agencies, should be promoted. One useful way is to create decision-support tools assessing the behaviour of potential microbial hazards along the food chain and their impact on public health. Their use might depend on the availability of user-friendly software, which encompass predictive modelling tools and risk assessment modules to allow different users to retrieve information from them in a rapid and convenient way. The performance of risk-based metrics and the establishment of microbiological criteria could help to identify critical steps along the food chain that influence on the final risk associated to a specific pathogen. Throughout this paper, some examples on how to elucidate microbiological criteria basing on established risk-based metrics (namely, Performance Objectives and/or Food Safety Objectives) set as (i) numerical limit of pathogen concentration; (ii) frequency or proportion terms; and (iii) in qualitative to non detectable values.
Workshop Food Safety Challenges for Mediterranean Products, 2014/06/10-11, Zaragoza (Spain)